Ab-initio study of structural, electronic, elastic and mechanical properties of RuAl1−xGax (x=0, 0.25, 0.50, 0.75 and 1). (March 2015) - Fatima, Bushra; Chouhan, Sunil Singh; Acharya, Nikita; Sanyal, Sankar P.
Abstract: We have used special quasirandom structure to study the structural, electronic, elastic and mechanical properties of RuAl1− x Ga x alloys for different compositions ( x =0, 0.25, 0.50, 0.75 and 1) using a FP-LAPW method based on Density Functional Theory. The exchange and correlation potential is treated within the generalized gradient approximation. Ground state properties such as lattice constant ( a 0 ), bulk modulus ( B ), its pressure derivative ( B ′) and elastic constants are calculated. The ductility of these alloys has been analyzed by calculating the ratio of B / G H, Cauchy pressure ( C 12 – C 44 ) and Frantsevich rule. From this study RuAl and RuGa are found to be brittle, but their alloys show ductile behavior; RuAl0.50 Ga0.50 is found to be most ductile. Mechanical properties such as Poisson's ratio ( σ ), Young's moduli ( E ), and the ratio of elastic anisotropy factor ( A ) are estimated. We have also correlated the ductility and bonding behavior of these alloys. Graphical abstract: Variation of elastic moduli with concentration x of Ga of RuAl1− x Ga x . Highlights: The DFT calculations have been performed for RuAl1− x Ga x alloys using SQS approach. We analyzed that RuAl and RuGa are brittle while its alloys are ductile. Ductility is analyzed using Pugh's rule, Cauchy's pressure, and Poisson's ratio.